METHODOLOGICAL SUPPORT FOR IMPROVING THE METHODOLOGY OF PREPARING FUTURE SPECIALISTS FOR PROFESSIONAL ACTIVITY IN A DIGITAL EDUCATIONAL ENVIRONMENT (International journal of artificial intelligence, 2024)
In this article, further development of the education system in our country, enrichment of its content based on news, establishment of the activity of educational institutions in a way that aims at effective and vital goals, use of electronic information and educational resources, and education of the educational process are discussed. attention is paid to the issues of provision.